(untitled) (Economics and region, 2016)
In the article the state of crediting of enterprises of agroindustrial complex of Ukraine is analysed after 2012-2015 r.r. Certainly basic problems of crediting and suggestions are grounded in relation to the improvement of the credit providing of agricultural commodity producers.